Select all statements below which are true for all invertible n×n matrices AA and BB

a. (A+A^-1)^3=A^3+A^-1
b. ABA^-1=B
c. A^8 is invertible
d. A+In is invertible
e. (In+A)(In+A^-1)=2In+A+A^-1
f. (A+B)(A−B)=A^2−B^2

Answer :

LammettHash

(a) is false. Consider the identity matrix, [tex]A=I[/tex]. Then

[tex](I+I^{-1})^3=(2I)^3=8I[/tex]

bu

[tex]I^3+I^{-1}=I+I=2I[/tex]

(b) is false. Since [tex]A[/tex] is invertible, we have

[tex]ABA^{-1}=B\implies (AB)(A^{-1}A)=BA\implies AB=BA[/tex]

but in general, matrix multiplication is non-commutative.

(c) is true. Let [tex]B=A^8[/tex]; then

[tex]B(A^{-1})^8=A^7(AA^{-1})(A^{-1})^7=A^7(A^{-1})^7[/tex]

[tex]B(A^{-1})^8=A^6(AA^{-1})(A^{-1})^6=A^6(A^{-1})^6[/tex]

and so on, down to

[tex]B(A^{-1})^8=AA^{-1}=I[/tex]

which is to say [tex]B^{-1}=(A^{-1})^8[/tex].

(d) is false. Consider [tex]A=-I[/tex], so that

[tex](-I)+I=0[/tex]

which is singular (i.e. determinant is zero), and thus not invertible.

(e) is true. It follows from the distributivity of matrix multiplication:

[tex](I+A)(I+A^{-1})=I^2+AI+IA^{-1}+AA^{-1}=I+A+A^{-1}+I=2I+A+A^{-1}[/tex]

(f) is false for the same reason as (b). Expanding the product gives

[tex](A+B)(A-B)=A^2+BA-AB-B^2[/tex]

but in general, [tex]AB\neq BA[/tex].

Other Questions